Red‐backed shrike (Lanius collurio) versus common cuckoo (Cuculus canorus): An example of ineffective cuckoo–hawk mimicry. Issue 12 (23rd December 2022) - Krausová, Ladislava; Veselý, Petr; Syrová, Michaela; Antonová, Kateřina; Fišer, Ondřej; Chlumská, Vanda; Pátková, Markéta; Pužej, Šimon; Fuchs, Roman
Abstract: The red‐backed shrike ( Lanius collurio ) used to be one of the most common hosts of the common cuckoo ( Cuculus canorus ). Nevertheless, during the last 30 years, there is increasing evidence from Central Europe that the occurrence of cuckoo chicks in shrike nests has become scarcer, and that in some locations they have disappeared completely. Multiple hypotheses have been suggested to explain this abandonment. Here, we test the hypothesis that shrikes vigorously attack adult cuckoos, potentially resulting in ineffective parasitism. Adult common cuckoos resemble in appearance the Eurasian sparrowhawk ( Accipiter nisus ), a common predator of small passerines. One hypothesis presumes that the cuckoo has evolved this mimicry to avoid attack by small passerines when searching for their nests. Our results show that shrikes defending their nests attacked cuckoos very vigorously, more often, and more intensively than they did sparrowhawks. In the presence of a sparrowhawk dummy, parent shrikes only produced alarm calls and flew over the dummy. This suggests that cuckoo–hawk mimicry is ineffective in the case of shrikes and that they attack them much more often than they do any other presented intruder. Therefore, this activity could possibly result in the abandonment of shrikes as potential hosts for cuckoos. Abstract : For the first time, we experimentally tested reaction of Czech red‐backed shrikes to the common cuckoo (nest parasite) and compared it with the reaction to the similarly looking Eurasian sparrowhawk (predator of adults) and the turtle dove (harmless intruder). As the shrikes are abandoned by cuckoo for 30 years in the Czech Republic, this topic can describe evolutionary changes in the relationship between parasite and host that can occur in a relatively short period of time. Despite absent evolution pressure, shrikes are still able to successfully discriminate between nest parasite—the common cuckoo, and similarly looking harmful predator of adults—the Eurasian sparrowhawk.